2014
DOI: 10.1177/1043659614550488
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Newly Diagnosed Breast Cancer Patients in Turkey

Abstract: Nurses should be aware of psychosocial difficulties suffered during the diagnostic phase and provide care for patients. It is important that nurses provide information about the diagnostic phase to women with breast cancer and encourage them to ask questions and express their feelings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…Fear (not lack of knowledge about symptoms, but a lack of knowledge that breast cancer is treatable) was directly linked by women in two studies to their decision to delay seeking medical diagnosis 10 25. Equally, social challenges described by women in this study in relation to social stigma, breakdown of intimate relationships, social isolation and role weakening have been well documented by studies in other LMICs 10 24 26–28…”
Section: Discussionmentioning
confidence: 53%
“…Fear (not lack of knowledge about symptoms, but a lack of knowledge that breast cancer is treatable) was directly linked by women in two studies to their decision to delay seeking medical diagnosis 10 25. Equally, social challenges described by women in this study in relation to social stigma, breakdown of intimate relationships, social isolation and role weakening have been well documented by studies in other LMICs 10 24 26–28…”
Section: Discussionmentioning
confidence: 53%
“…In Turkish society, cancer is a stigmatized disease. The results of the studies that have been conducted with patients with breast cancer in Turkey suggest that breast cancer is perceived as something that threatens life and that its prognosis is uncertain (Inan et al, 2016). Also, the Turkish patients with breast cancer avoided using the word "cancer" due to this stigma (Cebeci et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, cancer is perceived as a disease that is equated with death and suffering. The results of recent studies that have been conducted with patients with breast cancer in the diagnosis and treatment process showed that women avoid using the word “cancer” and that the negative perception still remains (Cebeci, Balcı Yangın, & Tekeli, ; Inan, Günüşen, & Ustün, ). With the increasing cure rates, this negative perception is expected to change.…”
Section: Introductionmentioning
confidence: 99%
“…The women wanted cancer-related anti-stigma campaigns to be organized. Results of studies on breast cancer patients in Turkey show that stigma is an important problem in cancer trajectory (2,29,30). In a society where people have a negative perception of cancer, it can be difficult for patients to complete their treatment and to express what they have experienced.…”
Section: Discussionmentioning
confidence: 99%